Magikon zōon Animal et magie dans l'Antiquité et au Moyen Âge - Coulon, Jean-Charles; Dosoo, Korshi (Bibliothèque d'Histoire des Textes, 2022)
The overlap of two marginal topics in history - magic and animals - may at first seem more marginal still, but the purpose of this volume is to demonstrate that from these vital margins we may find new perspectives on and understandings of ancient and mediaeval societies. Recent decades have seen increasing interest in magic and related topics. The publication of the corpus of Greek magical papyri by Karl Preisendanz and his collaborators (1928-1931), and the History of Magic and Experimental Science by Lynn Thorndike (1923-1958), marked a clear turning point. While the immediate impact of these publications was demonstrated by the increasing number of important works by authors such as E.R. Dodds (The Greeks and the Irrational, 1951) and A. Festugière (La Révélation d'Hermès Trismégiste, 1950-1954), the last thirty years have seen a resurgence of interest. Recent research has increasingly sought out new theoretical perspectives, focusing on the relationship between religion, ritual and magic, and on questions of materiality and transmission. The hitherto Eurocentric focus, influenced by Judeo-Christian conceptions of magic, has been thoroughly interrogated, leading to new approaches, and new vantage points from which to examine ancient and mediaeval societies. Similarly, animals have recently become important as subjects of history as part of the overall "animal turn" which has developed within several academic disciplines. Much of this interest stems from two works - Peter Singer's Animal Liberation (1975) and Jacques Derrida's L'Animal que donc je suis (2006). While these were works of philosophy, the increased attention they have brought to animals has encouraged several academics within the humanities and social sciences to re-evaluate the place of non-human animals within their research, studying them both in their interactions with humans and as worthy objects of inquiry in themselves. This volume thus brings together the contributions of a group of scholars invited to think about animals and the Animal through the texts and objects of magic and the other "occult sciences" in their respective geographical areas and chronological periods, in the Mediterranean basin and its surrounding regions, from the ancient world to the Middle Ages.